El coyote debajo de la mesa = The coyote under the table : folktales told in Spanish and English - Hayes, Joe.; Castro, Antonio, 1941- (El Paso, TX : Cinco Puntos Press, 2011)
A collection of ten classic tales from Northern New Mexico retold in Spanish and English.
If I were an eagle -- What am I thinking? -- The golden slippers -- Caught on a nail -- How to grow boiled beans -- The coyote under the table -- The tale of the spotted cat -- The little snake -- The magic ring -- The man who couldn't stop dancing.
Includes bibliographical references (as 'Notes to readers and storytellers') (pages 131-133).
Parellel texts in English and Spanish = Textos paralelos en ingles y espanol.
Keywords: Tales -- New Mexico; Cuentos populares -- Nuevo Mexico -- Literatura juvenil; Folklore -- Nuevo Mexico -- Literatura juvenil; Libros bilingues; Folklore; Spanish language materials -- Bilingual